2010
DOI: 10.1289/ehp.1002182
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Interleukin-10 in Ozone-Induced Pulmonary Inflammation

Abstract: BackgroundThe mechanisms underlying ozone (O3)-induced pulmonary inflammation remain unclear. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that is known to inhibit inflammatory mediators.ObjectivesWe investigated the molecular mechanisms underlying interleuken-10 (IL-10)–mediated attenuation of O3-induced pulmonary inflammation in mice.MethodsIl10-deficient (Il10−/−) and wild-type (Il10+/+) mice were exposed to 0.3 ppm O3 or filtered air for 24, 48, or 72 hr. Immediately after exposure, differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 47 publications
2
20
1
1
Order By: Relevance
“…1A–C), consistent with previous reports by ourselves and others [18], [22], [23], [41], [42]. Increases in BAL inflammatory cells were significantly reduced in TCRδ −/− versus WT mice after 48 (neutrophils) and 72 (neutrophils and macrophages) hours of exposure (Fig.…”
Section: Resultssupporting
confidence: 92%
“…1A–C), consistent with previous reports by ourselves and others [18], [22], [23], [41], [42]. Increases in BAL inflammatory cells were significantly reduced in TCRδ −/− versus WT mice after 48 (neutrophils) and 72 (neutrophils and macrophages) hours of exposure (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In the present study we found that baseline IL-10 levels in sputum of allergic asthmatics were significantly decreased compared to normal volunteers (p=0.007), and there was a similar trend for difference with atopic non-asthmatics (p=0.09). Studies of IL-10 knockout mice indicate that IL-10 appears to be protective against O 3 -induced neutrophilic inflammation and NFkB activation54. Therefore, suppressed baseline IL-10 in our atopic asthmatic cohort may have contributed to increased pro-inflammatory cytokine production after O 3 exposure.…”
Section: Discussionmentioning
confidence: 83%
“…The studies reported here used a 72-h ozone exposure period to examine the impact of IL-6 on neutrophil recruitment. Differences in the kinetics of O 3 -induced pulmonary inflammation have been reported depending on the precise outcome indicator examined (5,6). Hence, it is conceivable that the IL-6-dependent SAA3/IL-17A/G-CSF-mediated neutrophil recruitment observed in Adipo Ϫ/Ϫ mice exposed to ozone, as outlined in Fig.…”
Section: Discussionmentioning
confidence: 99%